Volatile Organic Compounds of the Plant Growth-Promoting Rhizobacteria JZ-GX1 Enhanced the Tolerance of Robinia pseudoacacia to Salt Stress - Li, Pu-Sheng; Kong, Wei-Liang; Wu, Xiao-Qin; Zhang, Yu (Frontiers in Plant Science, 2021)
Salt stress is one of the major abiotic stresses that affects plant growth and development. The use of plant growth-promoting rhizobacteria to mitigcate salt stress damage in plants is an important way to promote crop growth under salt stress conditions. Rahnella aquatilis JZ-GX1 is a plant growth-promoting rhizobacterial strain, but it is not clear whether it can improve the salt tolerance of plants, and in particular, the role of volatile substances in plant salt tolerance is unknown. We investigated the effects of volatile organic compounds (VOCs) from JZ-GX1 on the growth performance, osmotic substances, ionic balance and antioxidant enzyme activities of acacia seedlings treated with 0 and 100mm NaCl and explored the VOCs associated with the JZ-GX1 strain. The results showed that compared to untreated seedlings, seedlings exposed to plant growth-promoting rhizobacterium JZ-GX1 via direct contact with plant roots under salt stress conditions exhibited increases in fresh weight, lateral root number and primary root length equal to approximately 155.1, 95.4, and 71.3%, respectively. Robinia pseudoacacia seedlings exposed to VOCs of the JZ-GX1 strain showed increases in biomass, soil and plant analyser development values and lateral root numbers equal to 132.1, 101.6, and 166.7%, respectively. Additionally, decreases in malondialdehyde, superoxide anion (O2−) and hydrogen peroxide (H2O2) contents and increases in proline contents and superoxide dismutase, peroxidase and glutathione reductase activities were observed in acacia leaves. Importantly, the sodium-potassium ratios in the roots, stems, and leaves of acacia exposed to VOCs of the JZ-GX1 strain were significantly lower than those in the control samples, and this change in ion homeostasis was consistent with the upregulated expression of the (Na+, K+)/H+ reverse cotransporter RpNHX1 in plant roots. Through GC-MS and creatine chromatography, we also found that 2,3-butanediol in the volatile gases of the JZ-GX1 strain was one of the important signaling substances for improving the salt tolerance of plants. The results showed that R. aquatilis JZ-GX1 can promote the growth and yield of R. pseudoacacia under normal and salt stress conditions. JZ-GX1 VOCs have good potential as protectants for improving the salt tolerance of plants, opening a window of opportunity for their application in salinized soils.